Teachers’ Experiences in Learning Action Cells (LAC) as a Basis for Enhancing Professional Growth at Lagundi-CCL National High School - Angeles, Imee; Lauro , Julie Ann; Yaneza, Genefer (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the lived experiences of 31 teachers participating in Learning Action Cells (LAC) at Lagundi-CCL National High School, using a phenomenological research approach. The findings revealed that the LAC served as a platform for collaborative learning, where teachers actively engaged in meaningful discussions, shared professional knowledge, and fostered a supportive and enriching learning environment.The action-oriented nature of the LAC enabled teachers to translate learning into practice by applying strategies in real classroom contexts, setting professional goals, and implementing interventions that created tangible instructional impact. Continuous reflection and improvement were also emphasized, allowing participants to critically analyze outcomes, identify areas for development, and share best teaching practices.However, the study also identified several challenges, including differences in participant perspectives, time constraints, and limited resources. Despite these issues, specific LAC strategies proved valuable in sustaining professional learning. Design thinking and action research strengthened problem-solving skills, while data-driven decision-making supported evidence-based instruction. Likewise, peer coaching and mentoring relationships significantly contributed to collaboration and professional growth.In conclusion, Learning Action Cells provide a meaningful structure for collaborative learning, reflective practice, and action-based professional development. Although challenges exist, the strategies embedded within the LAC framework effectively address these constraints and enhance teaching practice. The study underscores the vital role of LACs in promoting continuous professional growth, collaboration, and improved instructional outcomes among teachers.